Ferric pyrophosphate citrate as an iron replacement agent for patients receiving hemodialysis. (3rd April 2017) - Fishbane, Steven; Shah, Hitesh H.
Abstract: Treatment of anemia remains an integral component in the care of patients with end stage kidney disease receiving dialysis. Currently, both erythropoiesis stimulating agents and iron replacement agents remain important anemia management strategies for patients undergoing hemodialysis (HD). Ferric pyrophosphate citrate (FPC) was approved by the U.S. Food and Drug Administration in January 2015 as an iron replacement product in adult patients receiving long‐term maintenance HD. FPC is administered to patients on HD through the dialysate. Multicenter randomized, placebo‐controlled phase three clinical studies (CRUISE 1 and 2) have found dialysate FPC to maintain hemoglobin level and iron balance in patients receiving chronic HD. Adverse events were similar in both the dialysate FPC‐treated and placebo groups. Another study showed a significant reduction in the prescribed erythropoietin‐stimulating agents dose at the end of treatment in the dialysate FPC‐treated group compared with placebo. These studies have shown that dialysate FPC is efficacious and well tolerated. In this article, we review clinical studies evaluating the efficacy and safety of FPC and also propose a protocol for iron replacement in HD units where dialysate FPC is to be used.